Invisible innovators: how low-income, first-generation students use their funds of knowledge to belong in engineering. Issue 1 (2nd January 2016) - Smith, Jessica M.; Lucena, Juan C.
ABSTRACT: Though engineering is often perceived as a pathway of upward mobility in the United States, very little is known about the experiences of undergraduate engineering students who come from low-income backgrounds or are the first in their families to attend college. The little research that does exist on low-income, first-generation (LIFG) engineering students is grounded in a deficiency perspective that emphasizes the barriers these students face: greater feelings of financial pressure and curriculum overload, along with lower family support, confidence in technical skill sets, satisfaction with instructors and satisfaction with the overall college experience. Our ethnographic research with LIFG students at a public engineering university and community college reveals that these barriers can create a sense of belonging uncertainty for them as engineering students. Yet our students were also able to draw on the funds of knowledge they acquired growing up in poor families and, when these funds of knowledge are validated, they establish a sense of belonging in engineering education and the profession.